A Guideline Tool for Ongoing Product Evaluation in Small and Medium-Sized Enterprises - Fouad Abdulameer Salman; Aziz Bin Deraman; Masita Binti Abdul Jalil (Institute of Advanced Engineering and Science, 2017)
As consumer demand for user friendly software increases, usability evaluation is crucial to develop software systems which are easy to learn and use. However, implementation of usability evaluation is challenging for small and medium-sized enterprises (SMEs) due to factors such as lack of technical expertise, knowledge and experience of methods and standards. This results in neglect, or poorly executed evaluations of projects, resulting in software that disappoints and frustrates clients. To overcome this loss of competitiveness, we propose here a visual incorporation tool derived from ISO standards that would assist software development teams in SMEs in understanding and implementing usability evaluations. It shows fundamental Usability Engineering (UE) and Software Engineering (SE) activities and artifacts relevant to the usability evaluation and software development process, with potential incorporation points being highlighted. Dependencies and relationships are shown by links between activities and artifacts. Additionally, convergent artifacts of both disciplines were identified and shown. Evaluation of the proposed tool was based on the questionnaire results of software development practitioners from SMEs.